A NEW SPECIES OF BEGONIA (BEGONIACEAE) FROM SOUTH SULAWESI, INDONESIA, AND AN AUGMENTED DESCRIPTION OF BEGONIA BONTHAINENSIS - Wisnu Handoyo Ardi; Daniel C. Thomas (Research Center for Biology, 2019)
ARDI, W. H . & THOMAS, D. C. 2018. A new species of Begonia (Begoniaceae) from South Sulawesi, Indonesia, and an augmented description of Begonia bonthainensis. Reinwardtia 18(1): 19−26. — Based on collections from South Sulawesi, Indonesia, an amended description of B. bonthainensis Hemsl. is provided, B. grandipetala Irmsch is placed in synonymy of B. bonthainensis, and the new species Begonia mattampensis Ardi & D.C.Thomas is described and illustrated. Provisional conservation assessments indicate an Endangered (EN) status for B. bonthainensis, an endemic of Mt. Lompobatang and several adjacent mountains at the tip of the Southwestern arm of Sulawesi, and a Critically Endangered (CR) status for Begonia mattampensis, a limestone endemic only known from the Pangkadjene Karst.